Effective Strategy for Sharia Financial and Business Management in The Month of Ramadan - Novitasari, Kartika; Al Farisi, Muhammad Salman (Sharia Business Management Department of STEBIS Bina Mandiri, 2024)
This research was conducted with the main aim of exploring effective strategies in sharia financial and business management during the month of Ramadan, with a special focus on developing practical guidelines for sharia business actors. In achieving this goal, this research uses holistic research methods, involving literature analysis, case studies, and in-depth interviews with financial experts and sharia business practitioners. The research results show that the integration of sharia principles in financial and business management has a significant impact on business performance during the holy month of Ramadan. Effective strategies involve the use of zakat funds as an instrument of community economic empowerment, sharia-based product innovation that is responsive to market needs, and the application of Islamic financial principles in asset and investment management. The conclusion of this research confirms that implementing proper sharia financial and business management can be the key to business success in the month of Ramadan. Apart from making a positive contribution to business performance, this strategy also encourages sustainable growth and creates a positive impact in society. Therefore, sharia business actors are encouraged to understand and adopt this strategy in order to optimize economic potential and provide significant added value during the holy month of Ramadan.